Nathan Glazer y Daniel P. Moynihan (eds.). Ethnicity, Theory and Experience, Harvard University Press, Cambridge, Massachussetts y Londres, 1975. Tercera edición de 1976. 531 pp. - Susana B. C. Devalle (El Colegio de México, A.C., 1977)
-